Spin-dependent recombination of the charge-transfer state in photovoltaic polymer/fullerene blends. (2nd October 2019) - Lukina, E. A.; Reijerse, E.; Lubitz, W.; Kulik, L. V.
ABSTRACT: Q-band electron spin echo (ESE) spectroscopy was applied for studying the spin-dependent recombination of charge transfer (CT) states in the benchmark organic photovoltaics (OPV) blend of poly(3-hexylthiophene-2, 5-diyl) and [6, 6]-phenyl C61 butyric acid methyl ester (P3HT/PC60 BM). Selective microwave excitation and a special protocol for ESE data treatment allowed to suppress the ESE signal of thermalised polarons and weakly coupled CT states and to address CT states with a relatively short distance between positive and negative polarons (1.5 nm < r  < 2.5 nm). Inversion of the in-phase ESE signal with increase of the delay after laser flash was observed for the regioregular P3HT + /PC60 BM − CT state at a temperature of 40 K. This effect is very similar to the inversion of the time resolved (TR) EPR spectrum of the same system obtained previously. Both effects can be explained by spin-dependent recombination of the CT state, with the recombination via the triplet channel proceeding much slower than via the singlet channel. For the regiorandom P3HT + /PC60 BM − CT state no ESE sign inversion was observed in an analogous experiment. The result suggests the importance of CT state formation via a triplet exciton, a process which was not considered previously for the P3HT/PC60 BM blend. GRAPHICAL ABSTRACT: